Efektivitas aplikasi Hellotalk terhadap kemampuan berbicara bahasa Inggris siswa - Muhammad Fadhil, Muhammad Fadhil ((JELE) Journal Of English Language and Education, 2023)
Social media has become the new way to socialize, not only between people from different cities nor regions, but it also lets us socialize on a worldwide scale. As it lets us socialize on a wide scale, students can take advantage of it by socializing with native speakers to improve their conversation skill. Social media creates a fun environment that removes the burden of students to practice conversation as it does in common ways. The researcher wants to know the effectiveness of HelloTalk and the role-play method for improving students’ conversation skill. Therefore this study also wants to find out the significance comparison between HelloTalk app and the role-play method for students’ conversation skill. This study used a quantitative method with a quasi-experimental research design. The study used two groups as its subjects: a control group that implemented the role-play method to assist students in conversation practice and an experimental group that integrated HelloTalk as part of its treatment. The research shows this method works well for developing students’ conversation skill. Compared to roleplay method, HelloTalk App is more effective to improve students’ pronunciation, intonation, grammar, and confidence. The experimental class students who received treatment using the HelloTalk App had their conversation skill improved more significantly compared to the role-play method as the control group.